A multi-method evaluation of interprofessional education for healthcare professionals caring for women during and after pregnancy. Issue 4 (4th July 2018) - Olander, Ellinor; Coates, Rose; Brook, Judy; Ayers, Susan; Salmon, Debra
ABSTRACT: This multi-method evaluation assessed the perceived impact of interprofessional workshops targeting enhanced collaboration between healthcare professionals who care for women during and after pregnancy. Current policy recommends partnership working to improve care for women and babies, however, there is little interprofessional education in this area. Five one-day workshops were delivered to 18 healthcare professionals (47.4% of the 38 healthcare professionals registered). The workshop was evaluated through questionnaires before and after the workshop measuring attitudes and willingness towards collaboration; observations of the workshops by a researcher and follow-up interviews 2 months' post-workshop to explore changes in practice. Workshops were attended by midwives, health visitors (trained nurses specialising in community care for children 0–5 years), dietitians, nurses, a general practitioner and a breastfeeding specialist. Attitudes and willingness to participate in interprofessional collaborative practice improved after the workshop. Observations made at the workshop included engaged participants who reported numerous barriers towards collaboration. Follow-up contact with 12 participants identified several examples of collaboration in practice resulting from workshop attendance. These findings suggest that the workshops influenced attendees to change their practice towards more collaborative working. Future work needs to confirm these results with more participants.